Impact of generalized heat and mass flux models on Darcy–Forchheimer Williamson nanofluid flow with variable viscosity. (5th September 2019) - Salahuddin, T; Muhammad, Shah; Sakinder, Sana
Abstract: In the current study, we analyze the 2D Williamson nanoliquid flow due to variable thickness surface embedded in permeable space. Cattaneo–Christov heat and mass flux assumptions have been employed for the embodiment of heat and mass equations. Flow is generated by an exponential stretchable sheet. The Darcy–Forchheimer model is considered to scrutinize the liquid flow in a porous medium. The case of prescribed exponential surface temperature of heat transfer is examined. A model is contrived to comprise the partial differential equations and then transform them into ordinary differential equations by imposing an appropriate non-dimensional similarity transformation. The bvp4c technique is used to execute the laborious non-linear equations. A numerical interpretation is manifested to incorporate the skin friction values. The significance of the effect on the involved parameters is presented in graphs and discussed in detail.